2017
DOI: 10.1039/c7sc02050c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the stereo-hindrance of a curcumin scaffold for the selective imaging of the soluble forms of amyloid beta species

Abstract: We demonstrate that tuning the stereo-hindrance of the phenoxy-alkyl chains at the 4-position of a curcumin scaffold could lead to certain selectivity for soluble Aβs over insoluble Aβs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 43 publications
6
81
1
Order By: Relevance
“…Over the past several years, we have synthesized numerous curcumin analogues CRANAD-Xs. 24 To investigate whether these analogues have similar a effect as CRANAD-17, we used the SPEED to test CRANAD-Xs (X= -3, -25, -44 and -102) ( Supplementary Fig.8,9). We found that these compounds could alter the 4G8 antibody recognition and lead to increased chemilumiescence intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several years, we have synthesized numerous curcumin analogues CRANAD-Xs. 24 To investigate whether these analogues have similar a effect as CRANAD-17, we used the SPEED to test CRANAD-Xs (X= -3, -25, -44 and -102) ( Supplementary Fig.8,9). We found that these compounds could alter the 4G8 antibody recognition and lead to increased chemilumiescence intensity.…”
Section: Resultsmentioning
confidence: 99%
“…CRANAD-Xs compounds were synthesized according to our previously reported procedures and compounds with purities more than 95% determined by analytical HPLC, were used for further evaluation. 17,24 Synthetic Aβ1-40 peptide was purchased from rPeptide and different forms of Aβ1-40 including monomer, oligomer and aggregate were prepared by our previously reported methods. 17 In Vivo Anti-inflammation Test in Transgenic Mice.…”
Section: Methodsmentioning
confidence: 99%
“…[61] The probe exhibited an ideal fluorescence absorption and emission at 630 and 750 nm, respectively. [63] Boron dipyrromethane (BODIPY) has attracted wide attention for its excellent optical properties and applications in biological imaging. More importantly, CRANAD-58 was capable of targeting soluble Aβ in vivo from 4-month-old APP/PS1 transgenic mouse.…”
Section: The Detection Of Aβ Oligomersmentioning
confidence: 99%
“…The probe CRANAD‐102 exhibits higher selectivity toward Aβ oligomers over Aβ aggregates both in solution and in vivo. Furthermore, this molecule could penetrate the BBB to detect Aβ oligomers at an early stage of AD …”
Section: The Fluorescence Detection Of Aβmentioning
confidence: 99%
“…Optical imaging, including NIRF imaging and two-photon imaging, are the most used methods for preclinical investigations of fundamental pathological questions and for therapy monitoring in drug development. In the past years, our group has developed a series of smart NIRF probes, CRANAD-X for Abs [38][39][40][41][42][43] , and numerous other "smart" (turn-on) fluorescence probes have also been reported 28,37,[44][45][46][47][48][49][50][51][52][53][54][55][56][57] . However, "smart" chemiluminescence probes are rare 58 and none has been applied for studying Abs.…”
Section: Introductionmentioning
confidence: 99%